Analysis of beer consumption in Monterrey metropolitan area: A censored response model - Villezca Becerra, Pedro A.; Moreno Treviño, Jorge O. (Estudios Económicos de El Colegio de México, 2000)
This study analyses the effect of household income and socioeconomic composition on household expenditure on beer. Tobit models are used in order to capture the response on the magnitude of beer purchases as well as the behavior of nonpurchasing households. The results indicate, without regard to income segment, that household income and education of the household manager determine beer consumption and have a greater effect on potential consumers.